Aplikasi Penentuan Pakan Udang Berbasis Android - Jasmawati Jasmawati (Fakultas Teknik Universitas Muhammadiyah Parepare, 2026)
Pond farmers in Pinrang district generally provide feed that is still traditional, such as when to give it and the amount of feed, so that each harvest yields less than optimal results. This research was designed to create a vaname shrimp feed guide application to make it easier for farmers to obtain information on ideal feed. This research uses quantitative methods with Android Studio as a text editor and Java as a programming language. Research shows that the application makes it easier for pond farmers to get information and guidance on shrimp cultivation. The results showed that on the 10th day the first pond had an average body weight of 1.65 grams using 104 kg of feed, the second pond had an average body weight of 1.55 grams using 62 kg of feed with an average increase of 0.1 gram every day